Residual Herbicide Movement in Soil Columns - Gómez-De-Barreda, Diego; Gamón Vila, Miguel; Lorenzo Rueda, Elena; Saez Olmo, A. (2017)
Atrazine, bromacil, diuron, simazine, terbuthylazine, terbumetone, terbutyrne and trifluran are selective residual herbicides on citrus and very common in Spanish orchards. As a first step to measure the herbicide penetration in soil and therefore the risk of contamination, soil columns (40 cm in length, 9 cm interior diameter) were packed with an altered, screened loam soil. Simulated treatments were made by pouring, with a pipette, a solution of the chemicals on the soil surface. After the application, irrigations were done until the appearance of drainage water. Herbicide analyses were performed, at five soil depths, using high performance liquid chromatography for diuron (limit of detection 0.04 ppm) and gas chromatography for the rest of the chemicals (0.01 ppm). The leaching potential, in decreasing order was: bromacil > atrazine > simazine > terbumetone > terbuthylazine > terbutryene = diuron > trifluralin